1998
DOI: 10.1017/s1355617798466104
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a case of phonological alexia with agraphia using the Auditory Discrimination in Depth (ADD) Program

Abstract: Phonological alexia and agraphia are acquired disorders characterized by an impaired ability to convert graphemes to phonemes (alexia) or phonemes to graphemes (agraphia). These disorders result in phonological errors typified by adding, omitting, shifting, or repeating phonemes in words during reading or graphemes when spelling. In developmental dyslexia, similar phonological errors are believed to result from deficient phonological awareness, an oral language skill that manifests itself in the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
5
24
1
Order By: Relevance
“…The lack of improvement with comprehension is inconsistent with prior work using similar treatments (Conway et al, 1998;Kendall et al, 2003). However, this difference can, in part, be accounted for by differences in variables, such as treatment intensity and frequency, outcome measures, and alexia severity.…”
mentioning
confidence: 72%
“…The lack of improvement with comprehension is inconsistent with prior work using similar treatments (Conway et al, 1998;Kendall et al, 2003). However, this difference can, in part, be accounted for by differences in variables, such as treatment intensity and frequency, outcome measures, and alexia severity.…”
mentioning
confidence: 72%
“…The LiPS program is arranged hierarchically and divided into three stages: (1) oral awareness training, (2) simple nonword training (e.g., single syllables), and (3) complex nonword training (2-3 syllables) [13]; [6] Word Attack 0 38 -Word Identification 10 10 -Lindamood Auditory Conceptualization [7] Total Converted Score 27 58 § 100 however, the subject was only able to complete the first two stages in the 74 hours. The patient was unable to progress to complex nonword training because of a significant speech-motor programming impairment.…”
Section: Treatment Descriptionmentioning
confidence: 99%
“…However, the benefits of prior knowledge decline as either the extent of network damage increases, or when, as in the present case of a right-handed person with a very large left-hemisphere lesion, little prior knowledge exists in the unaffected networks of the right hemisphere. In contrast, in a previously reported successful use of a form of phonological therapy involving a subject with acquired phonological alexia [13], the subject was left-handed and the dominant Broca's area was substantially preserved; functional imaging studies demonstrated that following treatment, greater engagement of both the right perisylvian regions and the left Broca's area was exhibited [35].…”
Section: Potential Treatability Of Components Of Language Impairment mentioning
confidence: 99%
See 1 more Smart Citation
“…While many may not agree with Van der Leij's perspective, the chapter is well presented and thought provoking. The author's unique application of common terms provides the reader with a refreshing opportunity to reflect on how Van der Leij's constructs of inflexible and flexible abilities fit with the reader's own views of dyslexia and the burgeoning evidence of neural plasticity being present across the life span when effective treatment paradigms or principles are utilized (Adair et al, 2000;Conway et al, 1998;Kendall, Conway, Rosenback, & Gonzalez-Rothi, 2003;Torgesen, Wagner, Rashotte, Alexander, & Conway, 1998). Chapter 4, John Stein, includes a succinct review of genetics and the roles such research may play in future diagnosis.…”
mentioning
confidence: 99%